The Influence of Key Audit Matters, Audit Fees, and Company Size on Audit Quality - Icih Icih; Trisandi Eka Putri; Nur Adlin Farhanah binti Mat Arof (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
This research aims to determine the influence of key audit matters, audit fees, and company size on audit quality. The method used in this research is quantitative using multiple linear regression and SPSS version 25. The population used in this research is property companies listed on the Malaysian Stock Exchange in 2021-2023. The sample in this research was sought using a purposive sampling method consisting of 45 companies. The data used is secondary data from property financial reports listed on the Malaysian Stock Exchange for the 2021-2023 period. The research results show that the key audit matters variable does not have a positive and significant effect on audit quality with a significance value of 0.945. Audit fees partially have a positive and significant effect on audit quality with a significance value of 0.004 and company size partially has a positive and significant effect on audit quality with a significance value of 0.000. Based on the analyzes it can be partially concluded: 1) the key audit matters variable does not have a positive and significant effect on audit quality. 2) audit fees partially have a positive and significant effect on audit quality. 3) Company size partially has a positive and significant effect on audit quality.